The RRM domain in GW182 proteins contributes to miRNA-mediated gene silencing - Eulalio, Ana (Oxford University Press, 2009)
Proteins of the GW182 family interact with Argonaute proteins and are required for miRNA-mediated gene silencing. These proteins contain two structural domains, an ubiquitin-associated (UBA) domain and an RNA recognition motif (RRM), embedded in regions predicted to be unstructured. The structure of the RRM of Drosophila melanogaster GW182 reveals that this domain adopts an RRM fold, with an additional C-terminal α-helix. The helix lies on the β-sheet surface, generally used by these domains to bind RNA. This, together with the absence of aromatic residues in the conserved RNP1 and RNP2 motifs, and the lack of general affinity for RNA, suggests that the GW182 RRM does not bind RNA. The domain may rather engage in protein interactions through an unusual hydrophobic cleft exposed on the opposite face of the β-sheet. We further show that the GW182 RRM is dispensable for P-body localization and for interaction of GW182 with Argonaute-1 and miRNAs. Nevertheless, its deletion impairs the silencing activity of GW182 in a miRNA target-specific manner, indicating that this domain contributes to silencing. The conservation of structural and surface residues suggests that the RRM domain adopts a similar fold with a related function in insect and vertebrate GW182 family members.